A Brief History of Blockchain Interoperability. - Belchior, Rafael; Süßenguth, Jan; Feng, Qi; Hardjono, Thomas; Vasconcelos, André; Correia, Miguel (Communications of the ACM, 2024)
Blockchain interoperability has emerged as a critical focus for the development of next-generation decentralized applications. Significant progress has been made in the past five years, particularly in addressing challenges like the security of cross-chain token transfers. Despite advancements, vulnerabilities in cross-chain bridges remain a significant concern, with over $3.2 billion in losses due to attacks. Continued research is needed to improve privacy, user experience, and security in cross-chain infrastructure, alongside collaborative efforts from industry and academia to fully unlock blockchain's potential in decentralizing society.